The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/membranes10090240
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Polyureas—A Novel Subclass of Poly(Ionic Liquid)s for CO2 Capture

Abstract: The growing concern for climate change and global warming has given rise to investigations in various research fields, including one particular area dedicated to the creation of solid sorbents for efficient CO2 capture. In this work, a new family of poly(ionic liquid)s (PILs) comprising cationic polyureas (PURs) with tetrafluoroborate (BF4) anions has been synthesized. Condensation of various diisocyanates with novel ionic diamines and subsequent ion metathesis reaction resulted in high molar mass ionic PURs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…PILs diversity is further enriched by the way of their monomer assembly, or more precisely, by their architecture ( Figure 4 ). The major architecture types of PILs are linear (a) [ 141 , 142 , 143 ], branched and/or hyperbranched (b) [ 132 ], and cross-linked (c) [ 140 ], where the branched are further subdivided into dendrimer (d) [ 144 ], star (e) [ 145 , 146 ], and cyclic (f) [ 147 ]. This variability in charge carrying group configurations and polymer architecture not only highlights the creativity of synthetic chemists, but also underscores the versatility of PILs with inexhaustible possibilities for their performance fine-tuning.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
See 2 more Smart Citations
“…PILs diversity is further enriched by the way of their monomer assembly, or more precisely, by their architecture ( Figure 4 ). The major architecture types of PILs are linear (a) [ 141 , 142 , 143 ], branched and/or hyperbranched (b) [ 132 ], and cross-linked (c) [ 140 ], where the branched are further subdivided into dendrimer (d) [ 144 ], star (e) [ 145 , 146 ], and cyclic (f) [ 147 ]. This variability in charge carrying group configurations and polymer architecture not only highlights the creativity of synthetic chemists, but also underscores the versatility of PILs with inexhaustible possibilities for their performance fine-tuning.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
“…Recently, cationic polyureas with tetrafluoroborate anions have been synthesized. It was shown that CO 2 sorption depends on the type of the cation and the structure of the diisocyanate, with the highest sorption of 24.8 mg g −1 at 0 °C and 1 bar [ 141 ].…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst was easily recoverable, usable more than five times, and its activity had no obvious loss and good stability (Scheme 6). Shaplov et al [56] synthesized a series of new poly (ionic liquid) containing cationic polyurea (PUR) and tetrafluoroborate (BF4) anions. Condensation of various diisocyanates with novel ionic diamines and subsequent ionic rede composition reactions yield the high mole mass ion PUR, which has high thermal stability (up to 260 °C) and glass transition temperatures in the temperature range of 153-286 °C.…”
Section: The Co 2 Absorption and Conversion Of Other Functionalized I...mentioning
confidence: 99%
“…Shaplov et al [56] . synthesized a series of new poly (ionic liquid) containing cationic polyurea (PUR) and tetrafluoroborate (BF4) anions.…”
Section: The Co2 Absorption and Conversion Of The Functionalized Ioni...mentioning
confidence: 99%